Respuestas
Respuesta dada por:
1
Tu problema matemático: Explicación paso a paso:
1*x+-4*y=1*6*x+1*y=1**1 | -1*y
1*x+-4*y=1*6*x=-1*y+1**1 | : 6
1*x+-4*y=1*1*x=-0.167*y+*0.167*1 | -1*1*x=-0.167*y+*0.167*1
1*x+1*1*x=-0.167*y+*0.167*-1+-4*y=0 | +4*y
1*x+1*1*x=-0.167*y+*0.167*-1=4*y
████████▀▀▀████
████████────▀██
████████──█▄──█
███▀▀▀██──█████
█▀──▄▄██──█████
█──█████──█████
█▄──▀▀▀──▄█████
███▄▄▄▄▄███████
✞༒Espero ayudarte༒✞
Preguntas similares
hace 2 años
hace 5 años
hace 7 años
hace 7 años
hace 7 años